IJCM_420A: Chronic morbidity and disability and its effect on quality of life among the institutionalized elderly in Mangalore, South India: A cross-sectional study - Nair Aparna; Rekha T; Unnikrishnan Bhaskaran; Hegde Rithvik; Mohlah Daksha; Rao Aiswarya; Rai Nihal; Yadunath Sivaguha P; Mithra Prasanna; Kumar Nithin; Holla Ramesh (Wolters Kluwer Medknow Publications, 2024)
Background: Senior citizens, or individuals over 60 years, constitute 8.6% of India's population. As a result of shifting family dynamics brought about by growing urbanization and globalization, these elderly populations are flocking to elder care centers. The objectives of this research are to ascertain the elderly's self-reported chronic morbidities, disabilities, and the relationship between these factors with their quality of life (QOL). Methodologys: This cross-sectional study was conducted among 110 residents of old age homes in Mangalore block of Dakshina Kannada district. The data was collected using a semi-structured questionnaire consist of, Indian Disability Evaluation and assessment Scale and the World Health Organization Quality of life Brief Version (WHOQOL BREF) questionnaire and the data obtained was analyzed using SPSS version 24. Odd's ratio was calculated, independent T test was used to compare the means across the groups and a 'p' value < 0.05 was considered as statistically significant. Results: In the current study 65.5% participants were female (N=72) and most of the study participants reported hypertension and musculoskeletal pain (41.8% & 36.7% respectively) as the major ailment they are seeking health care, followed by diabetes mellitus (20.0%), angina (12.3%), asthma (10.9%), COPD (6.4%) and heart attack (4.5%). There was a statistically significant association between age, male gender, and level of disability with quality of life. Age of the participant was found to be directly proportional to quality of life in 2 domains - psychological and social relationships. Male gender was found to be significantly associated with social relationships domain of quality of life. Conclusion: It was shown that there was no clinically significant correlation between chronic morbidities and any dimension of quality of life, suggesting that the frequency and quality of health examinations delivered in the care homes were sufficient, which must carry on in the subsequent years.